Nature Is the Object of Satisfaction: Ambivalent Discourse of West Java Official Ecotourism Promotion (A Multimodal Ecolinguistic Study) - Reski Ramadhani; Hilmi Aulawi (Leksema: Jurnal Bahasa dan Sastra, 2026)
The presence of ecotourism is ideally related to conservation and sustainable relations between humans and nature. However, in digital promotion, its purpose has shifted toward a market-oriented tourism product, presented as an attractive destination for enjoyable experiences. The study aims to examine the discourse used to promote West Java ecotourism by analyzing how multimodal language constructs nature as an object of satisfaction. The study employs a qualitative descriptive approach within a multimodal ecolinguistic framework, integrating the Appraisal System and visual grammar, through representational, interactive, and compositional meaning analysis. The data consist of 93 images selected from West Java’s official Instagram posts on ecotourism, along with their captions, from the post-pandemic period during 2023-2025. The finding reveals that, in verbal analysis, Appreciation dominates the captions, with Engagement and Gradation strengthening it, suggesting that nature was promoted more for its aesthetic appeal and its ability to produce memorable experiences for visitors. The limited presence of Judgment indicates that ecological responsibility is only marginally emphasized.  Visually, human-nature interaction dominates, suggesting that nature is represented as a space to be entered, enjoyed, and experienced. The verbal-visual integration reveals an ambivalent ecolinguistics discourse, acknowledging the place's beauty but not encouraging people to protect it.